EFFECTIVENESS OF EN BLOC REMOVAL OF FIBRINOGEN-RICH COMPONENT OF CYSTOID LESION FOR THE TREATMENT OF CYSTOID MACULAR EDEMA. Issue 1 (January 2020) - Imai, Hisanori; Otsuka, Keiko; Tetsumoto, Akira; Miki, Akiko; Nakamura, Makoto
Abstract : Purpose: To introduce the methodology and outcomes of en bloc removal of the component of cystoid lesion during pars plana vitrectomy as a novel approach for the treatment of cystoid macular edema and show evidence that the component is an aggregation of fibrinogen by mass spectrometry analysis. Methods: The surgical en bloc extraction of the component of cystoid lesion was performed for cystoid macular edemas secondary to diabetic retinopathy and retinal vein occlusion. Perioperative change of best-corrected decimal visual acuity, and the central retinal thickness and the continuity of subfoveal ellipsoid zone and external limiting membrane on optical coherence tomography were evaluated. Mass spectrometry was performed for the identification of protein constituting the component. Results: Six eyes from six patients were included in the study. In all cases, central retinal thickness was improved after the surgery and remained stable during the follow-up period. Best-corrected decimal visual acuity and the continuity of ellipsoid zone and external limiting membrane were kept in all cases during the follow-up period. The mass spectrometry analysis disclosed that the component was composed of fibrinogen. Conclusion: The en block removal of the component of cystoid lesion combined with pars plana vitrectomy may be a promising option for treatment of cystoid macular edema. The component of cystoid lesion is presumably a fibrinogen aggregate. Abstract : Supplemental Digital Content is Available in the Text.The novel findings of this study are that the extraction of the component of cystoid lesion may be useful for the treatment of cystoid macular edema secondary to diabetic retinopathy and branched retinal vein occlusion, and that the component comprised an agglomerated fibrinogen.